Implementasi Teknologi Blockchain dalam Pengembangan Aplikasi Web Terdesentralisasi untuk Pengelolaan Data Pos Pelayanan Terpadu: Studi Kasus: Posyandu Mawar Lingkungan Gibug - Qomaruddin, Nurhadi; Gerhana, Yana Aditia; Taufik, Ichsan; Slamet, Cepy; Firdaus, Muhammad Deden (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2025)
The Integrated Service Post (Posyandu) is a community-based health service established by the government, playing an important role in monitoring child health, including efforts to reduce infant and child mortality rates. However, data management at Posyandu is generally still conducted manually using paper-based records, making it prone to data loss and inefficient in terms of access and tracking. One common approach to overcoming these challenges is the use of distributed data systems, which allow data storage and processing to occur across multiple computers in different locations. Nevertheless, many of these systems still rely on centralized servers, making them vulnerable to data breaches and manipulation due to the single point of storage. To address this issue, this research proposes the development of a decentralized web application based on blockchain technology as a solution for secure, transparent, and traceable data management. The application is developed using smart contracts written in Solidity, deployed on the Ethereum blockchain, with Hardhat as the backend framework and React.js as the user interface. The system was developed using a prototyping methodology and evaluated through black-box testing to assess its functional performance. Test results show that the application is capable of managing data effectively, while maintaining a high level of security and transparency. By adopting blockchain technology, the system enhances the effectiveness and efficiency of Posyandu’s data management, while ensuring data integrity and traceability within a decentralized environment.